The Role of Community Police Officer (Bhabinkamtibmas) in Preventing Crime of Motor Vehicle Theft at the Purwakarta City Police - Ignasius Wira Leburaya (Advances in Police Science Research Journal, 2020)
The increasing number of motor vehicle theft criminal acts in Purwakarta district and the lack of public vigilance make the crime that happens to be high too. And the pattern of prevention which is prioritized by the National Police is more acceptable to the community than the repressive pattern so that the writer raises a thesis that focuses on how the role of bhabinkamtibmas in the prevention of criminal acts of curanmor which has the aim of describing the modus operandi of curanmor and factors affecting the role of bhabinkamtibmas in efforts to prevent criminal acts chancel. Writing this research uses a qualitative approach to the type of descriptive research. Data collection techniques with interviews, observations, and literature methods. There are primary and secondary data sources and theories used to analyze are management theory and communication theory. The results of the study found that the role of Bhabinkamtibmas in preventing criminal acts of fraud was carried out through coaching carried out to the community by giving appeals to the people of kamtibmas. While the efforts made by Bhabinkamtibmas through the Friday Friday activities. There are factors that influence Bhabinkamtibmas in carrying out their duties, namely internal factors consisting of human resources, facilities and infrastructure, and budget while external factors come from the community itself. Based on the discussion of the study, the writer advises the leadership to analyze and evaluate Bhabinkamtibmas personnel and have a standard for evaluating Bhabinkamtibmas members, emphasizing the provision of material to the public regarding the theft of motor vehicles, repairing facilities and infrastructure owned by Purwakarta city police, and provide rewards and punishment to members of Bhabinkamtibmas as motivating for work.